2012
DOI: 10.2967/jnumed.111.102293
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-PET of the Hepatocyte Growth Factor Receptor Met Using the 1-Armed Antibody Onartuzumab

Abstract: The over-expression and -activation of hepatocyte growth factor receptor (Met) in various cancers has been linked to increased proliferation, progression to metastatic disease, and drug resistance. Developing a PET imaging agent to assess Met expression would aid in diagnosis and monitoring responses to Met-targeted therapies. In these studies Onartuzumab (MetMAb), the experimental therapeutic one-armed monoclonal antibody, was radiolabeled with 76Br or 89Zr and evaluated as an imaging agent in Met expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 20 publications
(33 reference statements)
5
72
0
Order By: Relevance
“…The development and quality control of 89 Zr-PRS-110 provided results similar to those previously seen for 89 Zr labeling of non-anti-MET antibodies (19), underscoring the compatibility of anticalins with standard labeling protocols and facilitating their application as radiotracers.…”
Section: Discussionsupporting
confidence: 53%
“…The development and quality control of 89 Zr-PRS-110 provided results similar to those previously seen for 89 Zr labeling of non-anti-MET antibodies (19), underscoring the compatibility of anticalins with standard labeling protocols and facilitating their application as radiotracers.…”
Section: Discussionsupporting
confidence: 53%
“…89 Zr-db-/ 76 Brornartuzumab and 89 Zr-PRS-110 were developed and assessed for visualization of c-Met-positive tumors in preclinical models (28,29). Optimal imaging time points were identified to be between 2 and 5 d after tracer administration, thus hampering potential routine clinical use as diagnostic agents.…”
Section: Discussionmentioning
confidence: 99%
“…There was significant correlation between Br-onartuzumab tumor uptake and tumor c-Met expression levels. In addition, higher tumor uptake was achieved using 89 Br-onartuzumab at later time points and had higher tumor-to-muscle ratios, suggesting that 89 Zr-onartuzumab would be better suited to image c-Met for diagnostic and prognostic purposes (Jagoda et al, 2012).…”
Section: F Tumor Microenvironment Imagingmentioning
confidence: 99%
“…A study in non-small cell lung cancer patients whose tumor was positive for c-Met showed that onartuzumab can prolong survival (Surati et al, 2011). Jagoda et al (2012 Zr and evaluated the ability to image c-Met-expressing tumors in mouse xenografts models.…”
Section: F Tumor Microenvironment Imagingmentioning
confidence: 99%